SOCIOLOGY OF CHILDHOOD - Sternheimer, Karen (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Typically children are only studied as victims or perpetrators of social problems, but in this course we will consider children in many additional contexts. We will begin by examining the meaning(s) of childhood and how it has changed over time. Then we will consider the many social contexts of childhood, including family, school, race, class, and gender. We will also pay special attention to why the relationship between youth and popular culture is routinely viewed as problematic, how children are discussed within the popular press, and examine how public policy is formulated in response to this and other issues. In short, this course will examine how children are not just socialized by adults, but also shape their own (and adult) experiences.